EFFECT OF DISCOVERY LEARNING MODEL TO CRITICAL THINKING SKILL AND COGNITIVE OUTCOME LEARNING STUDENTS SMP - Tota Tota Martaida; Nurdin Bukit; Eva Marlina Ginting (Universitas Negeri Medan, 2018)
This study aims to determine: students' critical thinking skills and student cognitive outcome learning with discovery learning model and conventional learning. Quasi experimental research was conducted using pretest-posttest control group design. The sample in this research is the experimental class treated with the discovery learning model and the control class apply the conventional learning chosen by simple random sampling. The instrument used is an essay test based on the indicator of critical thinking ability and outcome learning test based on bloom revision. Data in this research is analyzed by using t test. The results show that: The students' critical thinking ability which is taught by discovery learning is better than students who are taught by conventional learning and students cognitive outcome learning which is taught by discovery learning better than students who are taught by conventional learning